Study of interleaver for turbo trellis code modulation - Goh, Leng Meng. (2008)
In this project, three different interleaver designs will be studied and will be used to replace the existing interleaver proposed by Robertson and Worz. In their design, the interleaver just maps the even position symbols to even position ones and odd position symbols to odd ones; or even-odd and odd-even.